2022
DOI: 10.1038/s41598-022-06652-3
|View full text |Cite
|
Sign up to set email alerts
|

A multi-objective optimization using response surface model coupled with particle swarm algorithm on FSW process parameters

Abstract: In this study, multi-objective optimization of mechanical properties in friction-stir-welding of AH12 1050 aluminum alloy is performed using a combination of the response surface method and multi-objective particle swarm optimization algorithm. The process parameters are considered as tool pin diameter, shoulder diameter, rotational speed, feed speed, and tool tilt angle. The heat-affected zone’s yield strength, fracture strain, impact toughness, and hardness on the advancing and retreating sides are selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In a related development, Kahhal et al optimized and predicted the process parameters of friction stir welding of AH12 1050 using response surface algorithm coupled with PSO model. It was reported that that the hybrid model indicated superior prediction accuracy 53 . The prediction efficiency of HHO coupled with generalized neural network was reported in the literature 54 to predict the abrasion resistance of ultra-strength martensitic steel.…”
Section: Resultsmentioning
confidence: 99%
“…In a related development, Kahhal et al optimized and predicted the process parameters of friction stir welding of AH12 1050 using response surface algorithm coupled with PSO model. It was reported that that the hybrid model indicated superior prediction accuracy 53 . The prediction efficiency of HHO coupled with generalized neural network was reported in the literature 54 to predict the abrasion resistance of ultra-strength martensitic steel.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, fewer experimental trials can yield more quantitative information. Taguchi's method has been used in various fields, including renewable energy generation and energy storage systems [38][39][40][41] .…”
Section: List Of Symbolsmentioning
confidence: 99%
“…Recent investigations on predicting the hydrogen storage in MOFs highlight seven significant crystallographic features of MOFs which include crystal density, gravimetric and volumetric surface areas (GSA and VSA) of MOFs, pore volume (PV), pore and cavity diameters (PLD and LCD), and void fraction (VF), proving sufficient for precise predictions 21,27,41,42 . Admitting the multi-objective particle swarm optimization's (MOPSO) [43][44][45] simplicity and moderate performance, we embedded the B-RFT with MOPSO to optimize the crucial crystallographic features of MOFs that enhance the hydrogen storage tradeoffs in MOFs. Subsequently, we identified 152 optimum combinations of features as a theoretical benchmark which is further matched with the 733,792 open-source MOF structures.…”
Section: Introductionmentioning
confidence: 99%